Remineralizing Dental Materials
Patent Information
- Application Number
- JP2021559656
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2019-04-08
- Filing Date
- 2020-04-08
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2040-04-08
Smart Images

Figure 0007635143000008 
Figure 0007635143000009 
Figure 0007635143000010
Abstract
Description
[Technical field]
[0001] The present invention relates to remineralizing dental materials having at least one cation and at least one anion configured as partner ions to form a remineralizing substance. Further subject matter of the invention are the uses of this dental material, the method for its use and the kit for its production. Summary of the Invention
[0002] Various dental materials are known for the conservative treatment of defects in hard dental structures. The aim of using the mineralising effect of such materials is to stabilise the natural dental hardness remaining, for example after invasive treatment, against further deterioration caused, for example, by bacteria. In this case, mineralization occurs when the material is depleted of Ca 2+ Or F - The release of specific ions such as , can be induced by the incorporation of appropriate counter ions from saliva onto or into the dental hard tissue. New inorganic solid substances with low solubility are then formed to replace the lost minerals in the dental hard tissue (mineral replacement). Another approach is to extract Ca from saliva. 2+ The aim is to form mineral solids, primarily hydroxylapatite or other apatites, without the need for incorporation of ions or phosphate ions. Here, in the prior art, so-called bioactive glasses are mainly used.
[0003] The mineralisation possibilities of materials based on the prior art are generally limited. The reason for this is, on the one hand, that the amount of suitable ions available, i.e. partially soluble, in the material in question (e.g. glass ionomer cement) is limited, and, on the other hand, that in the class of materials in question, due to the nature of the material, only a limited amount of ion source (e.g. composite material with bioactive glass) can be used under acceptable physical properties. The amount of ions released and / or the amount of mineral substitute formed is limited from such materials and, as a result, is not sufficient for sustained stabilization of dental hardness.
[0004] WO2017 / 161179A1 discloses a remineralizing composition consisting of a 60:40 mixture of Bioglass 45S5 and polyaspartic acid. It provides only low concentrations of remineralizing ions. Furthermore, there is a limit to the possible selection and combination of remineralizing ions and therefore to the nature of the remineralization.
[0005] US2010 / 0272764A1 discloses a polymerizable dental resin composite with remineralization capabilities. The composite includes microcapsules containing calcium nitrate solution, potassium hydrogen phosphate solution, and sodium fluoride solution, respectively. The microcapsules contain an aqueous solution of calcium nitrate, potassium hydrogen phosphate, and sodium fluoride, and these ions are released through the capsule's semipermeable membrane due to their concentration gradient. The microcapsules are said to be produced by complex coacervation of oppositely charged polyelectrolytes. This also has the disadvantage that the concentration of released ions is low.
[0006] The aim of the present invention is to produce a dental material of the above mentioned kind which allows for effective remineralisation.
[0007] To this end, the present invention proposes that at least one of the partner ions is multivalent and is included as a counterion of the coacervate. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0008] First, certain terms used in the context of the present invention are explained.
[0009] The present invention relates to remineralizing dental materials.
[0010] Remineralization and demineralization are alternating biological processes between the teeth and the oral cavity, in which mineral ions are released and re-uptaken via saliva. Demineralization refers to the loss of tooth minerals, typically due to the dissolution of mineral elements, mainly hydroxyapatite, caused by acids (e.g., caries-causing plaque), and represents a major process in the formation of caries. (P. Shellis in:Karies [Caries], H. Meyer-Lueckel, S. Paris, KR Ekstrand eds., G. Thieme Verlag, 2012, p.23).
[0011] Remineralization in the narrow sense includes the accumulation or loss of mineral material, primarily apatite-based, in areas of the tooth surface. (P. Shellis, loc. P. Shellis, loc. sit., pp. 23, 26; S. Twetmann, K.R. Ekstrand, loc. sit., p.210). In the case of tooth substance previously damaged by demineralization, this type of remineralization process leads to a certain repair of the defect. The replacement material may grow onto the existing apatite crystals in the tooth, but new apatite crystals may also form. Current research suggests that even low concentrations of fluoride may stimulate the natural remineralization process.
[0012] Remineralization in the sense of the present invention refers to any process whereby mineral matter is added, through a process of precipitation, to existing dental hardness that may have been damaged by demineralization. This precipitation may result in growth of pre-existing apatite crystals within the dentin or may lead to the formation of new inorganic material at the site of remineralization. Suitable inorganic materials may be apatite-derived materials or other biocompatible compounds with low solubility. They are referred to in the present invention as remineralizing substances.
[0013] Dentin refers to the mineral-containing tooth substances such as enamel, dentin, and dental cement.
[0014] Partner ions are cations and anions that can combine to form a remineralizing substance.
[0015] Coacervation is a term that describes liquid-liquid phase separation. Ionic polymers or macroions (eg, ionic polyphosphates) can form coacervates with multivalent counterions (eg, calcium) to form a relatively polymer-rich phase within the polymer solution.
[0016] Coacervates are polyelectrolytes crosslinked via multivalent counterions. In aqueous media, the coacervate takes the form of a highly viscous phase. Depending on the high molecular weight of the parent polyelectrolyte, the coacervates take the form of liquid, viscous to viscoplastic materials that exist in phase separated form in aqueous media. Coacervates exist only within a certain range of ratios of the amounts of substance of polyelectrolyte to multivalent counterions and only when the concentration of polyelectrolyte exceeds a certain minimum value. If the proportion of counterions is too low or the concentrations of coacervate formers (multivalent counterions and polyelectrolytes) are too low, phase separation in water will not occur.
[0017] Suitable coacervates are formed from anionic or cationic polyelectrolytes and multivalent cations or multivalent anions. Suitable coacervates include an ionic polyelectrolyte and multivalent counterions that crosslink the polyelectrolyte.
[0018] The coacervates are preferably made by mixing an aqueous solution of an anionic or cationic polyelectrolyte with an aqueous solution of multivalent cations or anions. Here, an anionic polyelectrolyte is mixed with a multivalent cation, and a cationic polyelectrolyte is mixed with a multivalent anion.
[0019] The coacervate forms a separate, highly viscous liquid phase in the mixture. The coacervate is preferably separated. This is achieved in each case by any suitable known method, such as decantation or centrifugation. The separated coacervate is preferably purified. This is preferably achieved by simple washing with a solvent, preferably water.
[0020] The present invention has discovered that partner ions of remineralizing materials that have high mineralizing capacity for dental hardness become available in the dental material if at least one of these partner ions is present as a counter ion in the coacervate. With regard to the mineralizing effect, the aim is to stabilize the natural dental hardness remaining, for example after invasive treatment, against further deterioration, for example induced by bacteria. In this case, mineralization is Ca 2+ Or F - Certain ions such as may be released from the material and induced by the appropriate partner ions from saliva on or in the dental hard tissue. New inorganic solid materials with low solubility are then formed, replacing the lost minerals in the dental hard tissue (mineral replacement).
[0021] Conversely, the mineralization potential of known dental materials is limited. One reason for this is that known ingredients with a mineralizing effect can only be added to dental materials in limited amounts without impairing other physical properties of said materials. A further reason is that, for example, in the case of known glass ionomer cements, the speed and amount at which ions can be delivered into and / or out of the corresponding dental material is limited.
[0022] For use, the dental material according to the invention with mineralizing effect is advantageously present in liquid or pasty form, but at least in a adaptable form, and is applied in this form to the dental hardness to be treated. There, it is manually applied to a surface and potentially shaped. The remineralization process tends to be very slow, so the material should remain at the application site for at least some time after curing. For a method of use particularly suitable for long-term therapeutic success, the material must harden after a certain time and the working time must be sufficient for manual manipulation of the material. In that case, the hardened form of the material also serves to protect the remineralized site from mechanical and / or chemical degradation. Before hardening and, if envisaged, after hardening, the material should be able to supply ions for the mineralisation of the dental hardness with the formation of mineral replacement.
[0023] In one preferred method of use, dental materials having mineralization potential are to be used rationally for the stabilization of enamel. This may be enamel that has been partially deteriorated by caries processes, enamel in areas exposed to invasive dental treatments, or regions undermineralized due to enamel misformation (e.g., MIH). Desirable dental materials will mineralize unmineralized (undermineralized) dental hardness in contact with them and cover such areas for at least the period of time required for mineralization of the enamel areas. A permanent fixation in the sense of a filling material is also conceivable. Use results in stabilization of tooth structure, including remineralization and physical protection for the period required for remineralization. In such uses, the material in question ideally also adheres at the site to be treated.
[0024] A further desirable specific application of mineralized dental materials is for the stabilization of existing or remaining dentin. Such applications are directed, for example, to exposed dentin in exposed cervical areas. This particular clinical situation is known to be difficult to manage as achieving a durable impermeable seal in this area is very challenging. This is especially true in the treatment of cervical caries, which is clinically difficult to treat. In this application too the material has both a physical protective effect and a mineralizing effect and thus acts as a stabilizing agent. Again, for clinical reasons, the material should be capable of being adhesively fixed to dentin at the point of use.
[0025] Another preferred use of such materials is directed to their usefulness as reline materials, particularly where deep cavities are present and, under certain circumstances, where demineralized dentin remains within the cavities. Again, the aim is a stabilising effect and durable protection. A problem with prior art materials is that relines based on inorganic materials do not always have sufficient chemical stability and / or do not bond, or only bond poorly, to the substrate.
[0026] A preferred requirement for the mineral substitute formed is that it has, from a chemical standpoint, at least the same stability to an acidic aqueous environment as dental hardness (hydroxyapatite), and more preferably it has greater stability. Stability to an acidic aqueous environment refers to being less soluble in such a medium. Forming such a chemically stable mineral substitute can prevent the material from dissolving, for example, in the face of microbial exposure or acid production.
[0027] In the present invention, it is preferred that one of the partner ions is multivalent and is included as a counter ion in the coacervate, and the second partner ion is included in the aqueous solution.
[0028] In this embodiment, a second polyelectrolyte may additionally be included, preferably having a different charge from the polyelectrolyte of the coacervate. If the polyelectrolyte of the coacervate is a cationic polyelectrolyte, then the second polyelectrolyte is an anionic polyelectrolyte, and vice versa. It has been shown that the addition of such a second polyelectrolyte means additional deep mineralization of tooth tissue, particularly dentin. This has the advantage, especially in the case of demineralized dentin, that it can improve the mineralization potential via the depth of penetration of the partner ions contained in the coacervate, thereby improving remineralization deep into the dentin.
[0029] In the present invention, both of the partner ions may be multivalent and included as counter ions in the respective coacervates. More preferably, one of the partner ions is divalent, ie has two charges, with preferred charge numbers being +3, +2, -2 and -3.
[0030] The coacervate may contain monovalent cations / anions in addition to multivalent cations / anions. It may be preferred that a fraction of the multivalent or other monovalent cations have antibacterial properties. Suitable cations having these properties are, for example, silver or copper ions. It may be preferred that the multivalent or other monovalent anion fraction has a biological or other remineralization supporting effect. In particular, it is preferable that fluoride is contained as the monovalent anion.
[0031] The anionic polyelectrolyte for forming a coacervate with a polyvalent cation may be preferably selected from the group of organic polyelectrolytes consisting of:
[0032] Polymers and copolymers containing carboxylic, phosphoric, phosphonic and / or sulfonic acid groups, as well as their salts and their partial esters; preferably polycarboxylic acids, polyalkylene phosphoric acids, polyalkylene phosphonic acids, such as polyvinyl phosphonic acid and polysulfonic acids, as well as their salts and their partial esters; more preferably poly(meth)acrylic acid, polyaspartic acid, polyitaconic acid and polyglutamic acid, as well as their salts;
[0033] Acidic proteins, acidic protein derivatives, and salts thereof, preferably lysozyme or gelatin (type B);
[0034] Acid polysaccharides and their salts, preferably salts of carrageenan, pectin, alginic acid, and hyaluronic acid.
[0035] The anionic polyelectrolyte for forming a coacervate with a polyvalent cation preferably has an average molecular weight (weight average Mw) of 3 kDa to 1500 kDa, more preferably 5 to 500 kDa, even more preferably 8 kDa to 200 kDa, and even more preferably 8 to 50 kDa or less.
[0036] The polyvalent cation is preferably selected from the group consisting of mineral-forming cations; preferably metal cations; more preferably metals of groups 2A, 3B, 3A of the PTEs, and also lanthanides; more preferably Ba. 2+ , Ca 2+ , Sr 2+ , Tb 3+ , and Yb 3+ ; more preferably Ca 2+ and / or a mixture of metal cations with Ca 2+ .
[0037] For example, in a Ca-containing coacervate, part of the Ca 2+ In particular, Sr 2+ Mixed cation coacervates are also possible, such as those substituted with
[0038] Polyacrylic acid and Ca 2+ A preferred embodiment of an ion-based coacervate provides a pH of at least 5 and a polyacrylic acid concentration of ≧1 mg / ml, more preferably ≧10 mg / ml, to form the desired separable coacervate.
[0039] The cationic polyelectrolyte for forming a coacervate with a polyanion is selected from the group consisting of organic polyelectrolytes, preferably polymers and copolymers containing primary, secondary and / or tertiary amino groups, and salts thereof; preferably polyamines; more preferably polyallylamine, linear or branched polyethyleneimine, chitosan, polysine, and polyarginine, and salts thereof; more preferably polyallylamine hydrochloride (PAH).
[0040] One embodiment of a cationic polyelectrolyte-based coacervate is a combination of polyallylamine hydrochloride (PAH) with phosphate or hydrogen phosphate as the counterion. In this embodiment, in order to create the coacervate, it should be ensured that the polyallylamine is present in as protonated a form as possible and the phosphate ions are present in as deprotonated a form as possible.
[0041] The cationic polyelectrolyte for forming a coacervate with a polyvalent anion preferably has an average molecular weight (weight average Mw) of 3 kDa or more and 1500 kDa or less, preferably 5 kDa or more and 500 kDa or less, more preferably 8 kDa or more and 200 kDa or less, and even more preferably 8 kDa or more and 50 kDa or less.
[0042] The polyvalent anions are preferably selected from the group consisting of mineral-forming anions, preferably orthophosphate, diphosphate, metaphosphate, silicate, more particularly inorganic silicates, preferably ortho, ino, band gap silicates, and partially organically modified silicates, more particularly alkyloxysilicates, sulfate, tungstate, vanadate, molybdate, carbonate, more preferably orthophosphate, diphosphate, metaphosphate, sulfate, tungstate, vanadate, molybdate, and even more preferably orthophosphate and / or a mixture of orthophosphate with mineral-forming anions.
[0043] The dental material according to the invention is in one embodiment preferably a liquid and / or emulsion and / or suspension, and preferably has a dynamic viscosity of 50 mPas or more, preferably 100 mPas or more.
[0044] The dental material of the present invention, in another embodiment, is preferably a solid, more preferably a powder.
[0045] The dental material of the present invention is, in another embodiment, preferably a gel or a paste.
[0046] The dental material may contain 1-100 wt% of partner ions and coacervates, with preferred lower and / or upper limits being 5, 10, 15, 25 etc. to 95 wt%. The stated intervals of 5 wt % in each case can be combined in any way to form lower and upper limit ranges in the present invention.
[0047] The dental material of the present invention preferably contains water, preferably 5 to 95 wt %, with preferred lower and upper limits being 5, 10, 15, 25, etc., to 95 wt %. The 5 wt % intervals in each case can be combined in any way to form lower and upper limit ranges in the present invention.
[0048] In the present invention, the coacervate in one embodiment may have a moisture content of 0.1 to 90 wt %, preferably 1 to 75 wt %, and more preferably 5 to 60 wt %.
[0049] In a preferred embodiment, after drying, for example, the coacervate may have a moisture content of 0.1 to 50 wt%, preferably 1 to 25 wt%, more preferably 5 to 25 wt%.
[0050] In the present invention, the concentration of the polymer electrolyte that forms the coacervate and its counterion in the coacervate is preferably 10 to 100 wt%, with the preferred lower limit being 25 or 40, more preferably 45 wt%, and the preferred upper limit being 55 or 75, more preferably 85, 90, or 95 wt%.
[0051] In the present invention, it is preferable that a fluoride ion is contained as the partner ion.
[0052] In the present invention it is preferred that the partner ions in the dental material (especially prior to formation of the remineralised material) are present in a substantially soluble form.
[0053] The dental materials of the present invention may be of a self-hardening configuration.
[0054] According to the invention, dental materials having a working time and / or setting time according to ISO 9917:2007 of 1 to 5 minutes are preferred.
[0055] In the present invention, the hardened dental material is preferably self-bonding and has a shear bond strength to enamel and / or dentin of at least 3.5 MPa.
[0056] The hardened dental material preferably has a compressive strength according to ISO 9917:2007 of at least 50, preferably at least 100, more preferably at least 200 MPa, and a flexural strength of at least 20, preferably at least 25 MPa.
[0057] The dental materials of the invention have a high mineralization potential for dental hardness and, in a particularly preferred embodiment, form mineral substitutes with a solubility in acidic media at pH 4.2 below the solubility of hydroxyapatite.
[0058] The dental materials in the present invention may contain additives such as pigments, dyes, antioxidants, preservatives, fillers or other compatibility agents, which may be added, for example, to adjust rheology. To improve the mechanical properties, it is possible to incorporate inert inorganic or organic fillers into the dental material, such as silicates, glasses, ZrO2, BaSO4, SiO2, prepolymers, etc. Fillers capable of positively influencing mineralization can also be used. Examples of the materials mentioned here include ion-releasing glasses such as ionomer glasses and bioactive glasses, hydroxylapatite particles, amorphous calcium phosphate (ACP) and tetracalcium phosphate (TCP). In particular, the hydroxylapatite is preferably in the form of nanoparticles having an average particle size of 5 to 100 nm. Moreover, by adding water-soluble particles of the partner ions of the present invention, particularly salts of calcium, phosphate, and fluoride, more particularly CaCl2 particles and (NH4)2HPO4 particles, it is possible to achieve a further increase in the mineral content and ion reservoir of these species. Water-soluble citrate salts are also preferred additives. For coloring, it is possible to add inorganic or organic color pigments. These pigments can be used to match the color of the material to a dental hardness or to introduce contrast between the material and the tooth.
[0059] As further possible additives, it is possible to introduce monomers, such as (meth)acrylates, or polyelectrolytes containing double bonds into the system. The additional possibility of hardening the polyelectrolyte systems by a second hardening mechanism allows additional influence on the properties of the described dental materials. In some architectures, the polymerizable monomer units may be cross-linked with polyelectrolytes. It is also possible for the coacervates used to be partially functionalized.
[0060] In the present invention, the term "aqueous solution" also includes a solution in which water is homogeneously dissolved in, for example, an organic solvent. Such solutions preferably contain 10 wt% or more water, more preferably 50 wt% or more water, and most preferably the only solvent is water.
[0061] By polyelectrolytes is meant in particular polymers in which charged groups are attached either directly or via spacer groups to the polymer chain. These charged groups can be negatively charged groups or positively charged groups. Preferably, only charges of one sign are located on each polymer chain. Here, the number of charged groups per polymer chain may vary within wide limits. For example, the polymer chains of suitable polyelectrolytes may include monomer units that do not carry charge carriers as well as monomer units that carry charge carriers. Suitable polyelectrolytes are preferably at a concentration of 1 mg ml -1 It has a solubility of more than 1000 ppm.
[0062] Coacervates are generally made by exchanging the counterions of a dissolved polyion with counterions that form a coacervate with the polyion. This type of preparation process is accomplished by simply mixing the polyions in solution in water with the corresponding coacervate-forming counterions in solution in water. The resulting coacervate can be freed from excess residual ions by simple washing operations and isolated as a syrupy to highly viscous or viscoelastic body. In a simple example, the sodium salt of polyacrylic acid is mixed with CaCl2. Ca in solution 2+ Ion concentration and Ca 2+ When the ratio of carboxylic acid to carboxylic acid reaches a certain level, phase separation occurs and a liquid, hydrous coacervate is separated. The coacervate may be employed in the liquid state as a continuous / macro phase. A feature of the coacervates of the present invention is that they have variable water content. Water can be removed from the coacervate phase that separates from the solution, for example, until a solid is obtained. This water removal is reversible. The coacervate can then be used in ground form, preferably as a powder. The powder is preferably made by drying and then grinding the dried coacervate. Drying is for example carried out at temperatures below 250° C., preferably below 100° C., 60° C. under normal pressure and 40° C. under reduced pressure, or preferably by freeze-drying. Milling can be dry or wet, in a suitable liquid medium, using a variety of techniques described in the prior art. A further possibility is the use in the form of a suspension or emulsion. Powders, suspensions or emulsions may hereinafter be referred to collectively using the term "finely divided form".
[0063] In the following, for the sake of simplicity, the coacervates based on anionic polyelectrolytes will be referred to as coacervates a) and the coacervates based on cationic polyelectrolytes as coacervates b).
[0064] When a coacervate is contacted with an aqueous solution of ions (partner ions) that can form compounds with low solubility in water with the cross-linking counter ions of the coacervate, the compounds with low solubility slowly precipitate at the interface with the coacervate.
[0065] In one embodiment, the aqueous coacervate is a mixture of polyacrylic acid and Ca 2+ It is based on ions. In this embodiment, phosphate may be used as the partner ion. For mineralization, in this form, solutions containing (NH4)2HPO4 at concentrations between 10 mM and 250 mM, preferably 130 mM, have proven advantageous. In this embodiment, pH also plays a significant role in the formation of mineral replacement. During mineral replacement, the pH decreases without the use of additional buffering agents. The use of a buffer such as TRIS is beneficial to the properties of the dental material.
[0066] In another embodiment, the aqueous coacervate is based on polyallylamine phosphate ions. In this case, Ca is used as the partner ion. 2+ Ions may also be used. For mineralization, a solution containing CaCl2 at a concentration between 10 mM and 250 mM, more preferably 130 mM, has proven advantageous. In this embodiment too, the pH has a decisive effect on the formation of mineral substitutions.
[0067] In one embodiment, the tooth surface is contacted with a solution containing the partner ions for a period of time. The coacervate is then applied to this surface, conformed facially (eg, as a film), and left in place until sufficient mineralization of the dentin has occurred. Optionally, another type of coacervate can be applied to this treated surface.
[0068] In this use form, the coacervate is applied on the one hand as a viscous liquid. On the opposing surface of the teeth, the arrangement can be protected for a desired period of time to prevent premature loss of the coacervate layer. Alternatively, the coacervate can be finely divided and applied to tooth surfaces that have been treated with the partner ions. In this case, use as a powder is also possible, since there is always a sufficient amount of water in the oral environment, which is necessary for the mineralization process.
[0069] In another embodiment, the coacervate is mixed in finely divided form with a solution of the partner ions and applied in this form to the tooth surface to be treated. Again, mineral replacement is formed from the interface of the coacervate particles, which can also affect dentin.
[0070] The combination of coacervates based on oppositely charged polyelectrolytes primarily leads to the formation of highly crosslinked solid interpolymer complexes of these polyelectrolytes, which are insoluble in water. Second, mineral substitution occurs when appropriate counterions are selected. That is, the material solidifies to form an inorganic solid, the precursor of which becomes part of the starting components in the form of a coacervate.
[0071] In principle, the components comprising the coacervates a) and b) may be mixed with one another as liquid components, physically separated and then very rapidly form a solid. It may be more advantageous to use a finely divided coacervate that is mixed in the presence of water at the time of use. The working and setting times of such coacervate combinations can be controlled by selecting the particle or particulate size distribution. It is also possible to apply the coacervates layer by layer.
[0072] In a preferred embodiment, the finely divided components comprising the coacervates a) and b) are mixed in the presence of an aqueous solution and applied to the dentin to be treated. There it undergoes solidification, primarily as a result of the formation of insoluble interpolymer complexes. As the reaction proceeds further, mineral-substitute-forming ions are released from the coacervate and mineral substitutes are formed in the areas of exposure to the coacervate mixture and in the areas of the dental hard tissue.
[0073] In one form in which the dry milled components, including coacervates a) and b), are mixed together, it is necessary to mix them with water or an aqueous solution prior to application to the dentin in order to allow reaction. Mixing of the water or aqueous solution is preferably performed prior to application to the dentin, for example by hand mixing or by automated means such as mixing in a capsule.
[0074] The powder and water or aqueous solution are mixed in a weight ratio of preferably between 5:1 and 1:50, preferably 2:1 and 1:10, more preferably 2:1 and 1:2. In a preferred embodiment, the coacervates a) and b) are mixed as powders with water or an aqueous solution in a weight ratio (the sum of a) and b) of 2:1 to 1:10, preferably 2:1 to 1:1, more preferably 3:2.
[0075] Alternatively, individual powders or powder mixtures can be applied to a moist tooth surface where the reaction occurs as described above.
[0076] One preferred embodiment of these co-ground coacervates is a mixture of Ca-polyacrylic acid coacervate and polyallylamine-phosphate coacervate. For this mixed coacervate, a 1:1 mass ratio is advantageous. Mass ratios from 5:3 to 3:5 are also possible. The amount of optional mixed water is guided by the target mix concentration required for a particular application.
[0077] In another embodiment, a non-aqueous dispersion of a mixture of dry powders of components having coacervates a) and b) in a completely water-miscible solvent (e.g., glycerol) is mixed with additional aqueous components prior to use. This mixture is then applied to the tooth tissue to be treated, where the hardening and mineralization process takes place.
[0078] It may be preferred that aqueous emulsions of the components comprising the coacervates a) and b), in each case optionally containing further soluble mineral replacement-forming salts in the aqueous phase, are mixed with each other prior to use. This mixture is applied to the tooth tissue to be treated, where again the hardening and mineralization process takes place.
[0079] The aqueous emulsion of the coacervate or multiple coacervates as dental materials comprises at least 1% by weight of coacervate, preferably at least 2% by weight, more preferably at least 5% by weight.
[0080] Mixing, in each case, can be done manually or using automated mixing methods, for example by dispensing the two-component materials from a dual cartridge and mixing using a static or dynamic mixer.
[0081] In order to obtain an early bond between the tooth surface and the dental material, in one preferred method of use, the dental material to be treated is treated with an aqueous solution of a polyacid or polybase or a salt thereof before applying the components of the coacervate a) and b) mixed with one another. It is particularly preferred to treat the dentin surface with polyamide before applying the mixture of a) and b). In a further use, first an aqueous solution of a polyacid is applied to the dentin, then an aqueous solution of a polybase is applied, and finally a mixture of a) and b) is applied. The use of a polyacid or polybase as described herein prior to application of the dental material of the invention should be distinguished from the equally inventive addition of such a polyacid or polybase to the dental material of the invention itself.
[0082] Due to its mineral replacement forming and mineralizing properties, the dental materials of the present invention over time develop stronger interactions with the dental hardness, thus counteracting the destabilizing effects on the bond as a result of exposure to the environment. Such interactions include, for example, establishing a mineral replacement bridge between the dental material and dental hardness.
[0083] Since the amount of mobile ions contained in the coacervate is relatively high, the mineralization potential of the coacervate to dental hardness is correspondingly high. By selecting the combination of counterions in the coacervate, it is also possible to influence the nature of the mineral substitution and its chemical stability.
[0084] A further subject of the invention is a kit for producing a remineralizing dental material according to the invention, comprising the following components:
[0085] a first component comprising at least one coacervate having one of the partner ions as a counterion of the coacervate;
[0086] A second component containing water;
[0087] Here, a second of the partner ions is included as a free ion in the aqueous solution in the second component and / or as a counter ion of a second coacervate in one of the two components.
[0088] Preferably, at least one of the components is a solid, more preferably a powder.
[0089] In another preferred embodiment, at least one of the components is liquid, preferably having a dynamic viscosity at 23° C. of 10 mPas or more, more preferably 50 mPas or more, very preferably 100 mPas or more.
[0090] In another preferred embodiment, at least two of the components are pastes.
[0091] In another preferred embodiment, at least two of the components are gels.
[0092] In the present invention, it is preferred that at least one of the components, preferably at least two of the components, have a pH of 7 to 9 at 23°C.
[0093] The kit preferably comprises a further component c, which preferably has a pH of less than 7 and comprises an adhesion promoter. The adhesion promoter is preferably a polyacid or polyamine that is protonated to an extent of at least 10%. The use of polyacids or polyamines as described herein prior to application of the dental materials of the invention should be distinguished from the equally inventive addition of these materials to the dental materials of the invention themselves. In the context of the present invention, it is likewise possible for such components to have a dual function, on the one hand as adhesion promoters and, on the other hand, as constituents of the dental material itself.
[0094] Preferably, components a and b are stored in a device suitable for mixing, preferably a mixing capsule containing powders and / or liquids and / or a multi-compartment cartridge as part of a cartridge system for extruding the components through a mixing needle, preferably containing two pastes or two gels.
[0095] In a preferred embodiment, one of the partner ions is multivalent and is included as a counter ion in the coacervate, and the second partner ion is included in the aqueous solution. At least one of the components further comprises a second polyelectrolyte having a different charge than the polyelectrolyte of the coacervate.
[0096] In the context of the present invention, it is preferred that component a comprises at least one coacervate a) or b) and at least one polyelectrolyte which has a different charge than the polyelectrolyte of the coacervate and which is not present in the form of a coacervate.
[0097] In the present invention, it is preferred that component a comprises at least one powder of a coacervate containing a polyvalent anion as counterion and at least one powder of an anionic polyelectrolyte.
[0098] In the present invention, it is preferred that component a comprises at least one powder of a coacervate containing a multivalent cation as counterion and at least one powder of a cationic polyelectrolyte.
[0099] In the present invention, it is preferred that component a comprises at least one first coacervate powder comprising an alkaline earth metal ion, preferably a calcium ion, as a counter ion, and at least one second coacervate powder comprising a polyvalent anion as a partner ion.
[0100] A further subject of the present invention is a method for using a kit according to the invention, comprising the following steps: i. applying component b to the dentin and / or enamel, preferably as a liquid; ii. applying component a together with component b to the dentin and / or component b together with component b to the enamel, preferably as a powder, paste, gel, or viscous liquid.
[0101] The subject of the present invention is also a method for using a kit according to the invention, comprising the following steps: i. mixing component a with component b; ii. applying the mixture to the dentin and / or enamel, preferably as a paste or gel.
[0102] A further subject of the invention is the use of the dental materials according to the invention as sealants, coatings, relines and / or filling materials, as luting cements, for pulp caps, as bone cements, as dental lacquers, as fissure sealants, as desensitizing agents, as remineralizing agents in the prevention or treatment of carious lesions or for the preparation of such materials.
[0103] An embodiment of the present invention is given below.
[0104] method
[0105] Loss during drying The freshly synthesized coacervate was weighed and then stored in a vacuum drying cabinet (Thermo Scientific Heraeus VT6025) at 40°C and 50 mbar for at least 24 hours, and the loss on drying was calculated from the initial weighed mass and the final weight.
[0106] Thermogravimetry (TGA) Thermogravimetric analysis (TGA) was performed in air from 25°C to 1000°C at a heating rate of 10 K / min (STA 449FS Jupiter, Netzsch). The parameter evaluated was the mass loss up to 250°C, which is due to the residual moisture content (lyophilized powder).
[0107] Energy Dispersive X-ray Spectroscopy (EDX) The element contents were measured using the following instruments. SEM / EDX; TM 3000 Tabletop SEM, Hitachi, and Quantax EDX detector, Bruker) A freeze-dried powder was used.
[0108] Compressive strength The specimens were fabricated using a two-piece stainless steel mold containing six cylindrical holes measuring 4±0.02 mm in height and 2±0.01 mm in diameter. The mold was placed on a glass plate and dental material was introduced into the holes. Once the hole was filled with material, the hole opening was milled flat. The test specimens were placed in a mold and stored at 37°C and approximately 100% relative humidity for 1 hour. The specimen was then removed from the humidity chamber along with the mold. The mold was opened, and a test piece with a height of approximately 4 mm and a diameter of approximately 2 mm was taken out. The compressive strength was measured using a ZwickRoell universal testing machine (model Z 010 / TN2A) (compressive strength after 1 hour). To measure the compressive strength after 4 days, the demolded specimens were again stored in a humidity chamber at 37℃ and 100% atmospheric humidity for 4 days. The specimens were then removed from the humidity chamber and the compressive strength was measured using a ZwickRoell universal testing machine. Steady forward speed: 1.0 mm / min Compressive strength (CS) is calculated using the following formula: CS [MPa] = F / (π r 2 ) Where: F is the maximum force applied to the specimen, in Newtons; r is the radius of the test specimen (mm). The measurements were carried out on six test pieces, and the average value was calculated from the six measured values.
[0109] Shear adhesive strength To measure the shear bond strength (SBS), bovine incisors without dental pulp were embedded in a low-temperature polymerizing resin (Viscovoss GTS with MEKP MEH hardener; Voss Chemie). Immediately prior to use, the impacted teeth were wet polished (P120 sandpaper) down to the enamel or dentin and then wet repolished with finer sandpaper (P500). The teeth were stored in demineralized water before use. For the measurements, the teeth were removed from the demineralized water. Next, a two-piece Teflon mold (ISO / TS 11405:2003) with a 3.0 mm diameter hole was attached and fixed with a metal bracket, after which the dental material was filled. After filling, a Hostaphan film was applied, a glass slide was attached, and the tooth was fixed with a metal bracket. The filled molds were stored in a humidity chamber at 37℃ for 4 days and then demolded. The specimens were subsequently measured using a shear device and force-distance diagram measuring device (Z010 / TN2A, Zwick GmbH & Co., Ulm, Germany) according to ISO10477:2004 at a forward speed of 0.5 mm / min. Tests were performed on three specimens in each case.
[0110] Dynamic Viscosity Viscosity was measured at 23° C. using a dynamic plate / plate viscometer (Dynamic Stress Rheometer, Rheometric Scientific Inc.). The measurements were performed in steady stress sweep mode with gap sizes ranging from 0.1 to 0.5 mm and shear stress ranging from 0 to 50 Pa.
[0111] Mineralization / X-ray Diffraction (XRD) The dental material of Example 6 was allowed to harden in a thin layer. They were then stored in a humidity chamber at 37°C for 5 days. The dried material was mortarized and analyzed in this form by X-ray diffraction (Bruker D8, Discover).
[0112] From coacervates a) and partner ions in aqueous solution (examples 9 and 10) After the mineralization time was over, the mixture was centrifuged, decanted, and washed three times with 1.75 ultrapure water. The washed centrifugation residue was then dried at 37°C. When the dried products were examined using X-ray diffraction (XRD), it was found that all were powders and contained a mineral phase. In Examples 11 and 12, the mineral material was removed from inside the gel body and analyzed in this state by X-ray diffraction (Bruker D8, Discover).
[0113] Particle Size Measurement To measure the particle size distribution, 250 mg of freeze-dried and ground coacervate was dispersed in 20 ml of ethanol in an ultrasonic bath for 5 min. Next, the particle size was measured in ethanol containing impurities using a particle size distribution measuring device based on the Fraunhofer diffraction method (Laser Diffraction Particle Size Analyzer LS 13 320 with Universal Liquid Module, Beckmann Coulter).
[0114] The chemicals used were as follows: - Polyacrylic acid sodium salt solution (NaPAA15, Mw=15kDa), 35wt.% solution (Sigma Aldrich) - Polyacrylic acid (PAA100, Mw=100kDa), 35wt.% solution (Sigma Aldrich) - Polyallylamine hydrochloride (PAH15, Mw=15kDa), 15wt% solution (Polyscience) - Polyallylamine hydrochloride powder (Mw=17.5kDa, Sigma) - Trisodium citrate tetrahydrate (Sigma Aldrich) - Calcium chloride dihydrate (Roth) - Diammonium hydrogen phosphate (Sigma Aldrich) - Strontium chloride (Roth) - Sodium hydroxide (Merck) - Hydrochloric acid (Merck) - Ultrapure water (MilliQ, Merck Millipore) - Gelatin (300 bloom, a type)
[0115] Synthesis of polyacrylate-based coacervates (Examples 1-4) To the aqueous solution of sodium polyacrylic acid, an aqueous solution of calcium chloride or an aqueous solution of strontium chloride was slowly added with vigorous stirring. Phase separation was observed during the addition. After complete addition, the mixture was stirred for an additional 5 minutes and then allowed to stand for 10 minutes to allow phase separation to occur. The supernatant that formed was poured off and the remaining phase was washed three times with 400 ml each of ultrapure water. A viscous liquid was obtained. The pH was adjusted using hydrochloric acid and sodium hydroxide solutions. The amounts, concentrations, and pH values of the solutions used are shown in Table 1.
[0116] TIFF0007635143000001.tif58164
[0117] Synthesis of coacervates based on polyallylamine hydrochloride (Example 5) The polyallylamine hydrochloride aqueous solution was slowly mixed with the (NH4)2HPO4 aqueous solution under vigorous stirring. Phase separation was observed during the addition. After complete addition, the mixture was stirred for an additional 5 min and centrifuged at 7700 g for 3 min to allow further phase separation. The supernatant that formed was poured off and the remaining phase was washed three times with 10 ml each of ultrapure water. A viscous liquid was obtained. The pH was adjusted using hydrochloric acid and sodium hydroxide solutions. The amounts, concentrations, and pH values of the solutions used are shown in Table 2.
[0118] TIFF0007635143000002.tif46164
[0119] Water content / loss on drying of viscous liquids obtained in Examples 1, 4, and 5 The water content of the viscous liquid was determined by loss on drying. Loss on drying is reported as moisture content in Table 3a.
[0120] TIFF0007635143000003.tif44133
[0121] Ion content of freeze-dried samples of viscous liquid obtained in Examples 1, 4, and 5 The ion content was determined as the element content by energy dispersive X-ray spectroscopy (EDX). The residual water content of the freeze-dried viscous gels was measured by thermogravimetry (TGA). The residual moisture content and elemental contents are reported in Table 3b.
[0122] TIFF0007635143000004.tif38164
[0123] Preparation of coacervate powder
[0124] Coacervate Powder (P1) The water was removed from the viscous liquid of Example 1 by freeze drying. The resulting material was ground in a vibratory mill (Pulverisette 0, Fritsch) for 7 h, then in a mortar mill (Pulverisette 2, Fritsch) for 6 h, and finally in a ball mill (ball distribution: 55 × 16 mm, 14 × 25 mm, 4 × 40 mm) for 18 h. The residual moisture content of the resulting white powder was measured by TGA. The residual moisture content was 8% by weight. Particle size distribution is D 10= 1.0 μm, D 50 = 4.4 μm
[0125] Coacervate Powder (P2) The water content was removed from the viscous liquid of Example 5 by freeze-drying. The resulting material was ground in a vibratory mill (Pulverisette 0, Fritsch) for 7 h, then ground in a capsule mixer (1 ml, ball diameter: 3.15 mm, Silamat, Ivoclar-Vivadent) for 60 s, and finally ground in a capsule mixer (1 ml, ball diameter: 0.1 mm, Silamat, Ivoclar-Vivadent) for 60 s. The residual moisture content of the resulting white powder was measured by TGA. The residual moisture content was 8% by weight. Particle size distribution:D 10 = 2.4 μm and D 50 =24.6μm
[0126] Polyallylamine hydrochloride powder (P3) This powder is a second, cationic polyelectrolyte, which, in accordance with the present invention, can be used together with a coacervate containing an anionic polyelectrolyte to promote deep mineralization in the manner already described above and illustrated in the examples.
[0127] Example 6 Preparation of self-adhesive and self-hardening dental materials from coacervate powders P1 and P2 To prepare the dental material, 150 mg of powder P1 was mixed with 150 mg of powder P2. This powder mixture and a further 0.2 ml of water were introduced separately from one another into a mixing capsule (Applicap, DMG Hamburg). The powder and liquid were mixed for 20 seconds using a vibrating mixer (Silamat, Ivoclar Vivadent AG) to obtain a ready-to-use treatment. Immediately after mixing, the resulting treatment was expelled from the mixing capsule through the needle of the mixing capsule to effect treatment.
[0128] Example 7 Preparation of self-adhesive and self-hardening dental materials from coacervate powders P1 300 mg of powder P1 and 0.2 ml of (NH4)2HPO4 solution (130 mM, pH 9) were mixed manually with a spatula on a tray for approximately 30 seconds to prepare a ready-to-use treatment.
[0129] Example 8 Preparation of self-adhesive and self-hardening dental materials from coacervate powders P1 A ready-to-use treatment was prepared by manually mixing 300 mg of ground powder P1 with 0.2 ml of 130 mM (NH4)2HPO4 and 100 mM sodium citrate solution adjusted to pH 9 for approximately 30 seconds. Compared to Example 7, this material cured significantly faster.
[0130] Example 9 40 mg of ground powder P1 and 1.75 ml of 130 mM (NH4)2HPO4 solution adjusted to pH 9 were mixed manually with a spatula for approximately 30 seconds in a 2 ml reaction vessel (Eppendorf tube), briefly shaken, and then stored horizontally at room temperature for 5 minutes and 24 hours, respectively.
[0131] Example 10 40 mg of coacervate powder P1 was mixed with 1.75 ml of an aqueous solution (similar to Example 8) containing 130 mM (NH4)2HPO4 and 100 nM sodium citrate in a 2 ml reaction vessel (Eppendorf tube), briefly shaken, and then stored horizontally at room temperature for 5 min and 24 h, respectively.
[0132] Characterization The dental materials of Examples 6 to 8 were measured for compressive strength. The compressive strengths are reported in Table 4.
[0133] TIFF0007635143000005.tif27164The compressive strength was highest for the material of Example 7. For all dental materials, the compressive strength was higher 4 days after processing than 1 hour after processing.
[0134] Shear adhesive strength (SBS) For Examples 6 to 8, the shear adhesive strength was measured. The dental material is self-adhesive. The specimens cracked and deformed before they were sheared off.
[0135] Mineralization The mineralization of the mixtures of Examples 6, 9 and 10 was investigated using XRD. The mineral phases detected are reported in Table 5.
[0136] TIFF0007635143000006.tif29164
[0137] Usage example
[0138] Preparation of model materials For the following use cases, a model material of demineralized dentin was first prepared. Each model material consists of a solid gel at room temperature.
[0139] At 40° C., 10 g of gelatin (A type, 300 bloom) was dissolved in 90 ml of an aqueous solution containing 130 mM diammonium hydrogen phosphate and 100 mM trisodium citrate tetrahydrate at pH 9. The resulting gelatin solution was applied to a standard 24-well titer plate and allowed to cool to room temperature. Once at room temperature, the solid gel bodies were removed from the titer plate using a spatula and stored in aqueous solution.
[0140] Application of dental materials to model materials All dental materials were applied to the surface of the model material, i.e., the top surface of the disk-shaped gel body, and stored at room temperature in 10 ml of aqueous solution (containing 130 mM diammonium hydrogen phosphate and 100 mM trisodium citrate tetrahydrate, pH 9) so that the dental material and model material were covered with the aqueous solution, or stored in a conditioning cabinet at room temperature with 100% atmospheric humidity. After 2, 3, 4, 8, and 12 days, the gel bodies were removed and washed with ultrapure water. Next, a disk-shaped cross section of the gel body was prepared using a razor blade. The cross sections were optically examined to determine whether there was mineralized material below the surface of the model material and how deep this material extended into the model material.
[0141] Examples 11-13 In the same manner as in Example 6, a self-adhesive, self-hardening dental material was prepared. The powders / powder mixes and liquids used in this case are shown in Table 6 below. TIFF0007635143000007.tif32164
[0142] The liquid component used is an aqueous solution containing (NH4)2HPO4 and sodium citrate, as already used in Example 8.
[0143] In Examples 12 and 13, the powder mixture contains Powder P3 as a second cationic polyelectrolyte, which is used together with a coacervate containing an anionic polyelectrolyte (Powder P1) to promote deep mineralization in the manner already described above.
[0144] To prepare the dental materials, 150 mg of each powder / powder mixture and the liquid component were introduced separately from one another into a mixing capsule (Applicap, DMG Hamburg). The powder and liquid were mixed for 20 seconds using a vibrating mixer (Silamat, Ivoclar Vivadent AG) to form the ready-to-use treatment material. Immediately after mixing, the resulting therapeutic material was delivered from the mixing capsule through the needle of the mixing capsule and processed.
[0145] The dental material thus prepared was applied to model substances and mineralization was tested according to the following application examples.
[0146] Example 11 The dental material of Example 11 in Table 6 above was applied to the model materials and stored in aqueous solution as described.
[0147] After 4 days, light deep mineralization was evident. Deep mineralization was still minimal after 12 days (Fig. 1). Minerals formed in the gelatin were detected throughout the depth direction, including calcium, carbon, phosphorus, and oxygen (Fig. 2). This mineral was identified as hydroxylapatite by XRD (Fig. 3).
[0148] Example 12 The dental material of Example 12 in Table 6 above was applied to the model materials and stored as described in aqueous solution.
[0149] After only 3 days, significant deep mineralization is observed (Fig. 4). Dental materials applied to the gelatin surface bond to the surface, are stable, and do not degrade. The mineral formed can be identified as hydroxylapatite by XRD measurement (Fig. 5). Furthermore, the minerals formed in gelatin can be detected by EDX analysis: calcium, carbon, phosphorus, and oxygen (Fig. 6).
[0150] Example 13 The dental material of Example 13 in Table 6 above was applied to the model substrate and stored in the conditioning chamber as described.
[0151] After only 2 days, significant deep mineralization was observed (Fig. 7). This dental material bonds to the surface, is stable, and does not degrade. The mineral formed was identified as hydroxylapatite by XRD. [Brief description of the drawings]
[0152] [Figure 1] Photograph of deep mineralization in cross section of Example 11 after 12 days. An area of mineralization (milky white) is visible below the concave cut edge of the gel body. A short distance below that is an area of further mineral material (pale grey). [Diagram 2] SEM / EDX (cross section) of minerals formed in gelatin of Example 11 after 12 days. [Skalenbereich = scale range] [Diagram 3] XRD of the mineral formed in Example 11 after 12 days. [Figure 4] Photograph of deep mineralization in cross section after 3 days in Example 12. [Diagram 5] XRD of the minerals formed in Example 12 after 3 days. [Figure 6] SEM / EDX (cross section) of minerals formed in gelatin from Example 12 after 3 days. [Skalenbereich = scale range]. [Figure 7] Photograph of deep mineralization in cross section after 2 days in Example 13.
Claims
1. 1. A kit for making a remineralizing dental material having at least one cation and at least one anion configured as partner ions to form a remineralizing substance, at least one of the partner ions being multivalent and included as a counter ion in a coacervate, The coacervate comprises an anionic or cationic polyelectrolyte and a multivalent cation or a multivalent anion; Partner ions are cations and anions that can combine to form remineralizing substances, such as the following components: a. a first component comprising at least one coacervate having one of the partner ions as a counterion of the coacervate; b. a second component comprising water; and a second of the partner ions is included as a free ion in the aqueous solution in component b and / or as a counter ion of a second coacervate in one of the two components.
2. 10. The kit of claim 1, further comprising a second polyelectrolyte having a different charge than the polyelectrolyte of the coacervate.
3. 2. The kit of claim 1, wherein both partner ions are multivalent and are included as counter ions in the respective coacervates.
4. 4. The kit according to claim 1, wherein the anionic polyelectrolyte for forming a coacervate with a multivalent cation is selected from the group of organic polyelectrolytes and is selected from the group consisting of: a. polymers and copolymers containing carboxylic, phosphoric, phosphonic and / or sulfonic acid groups, as well as their salts and partial esters; b. Acidic proteins, acidic protein derivatives, and salts thereof; c. Acid polysaccharides and their salts.
5. 5. The kit according to claim 1, wherein the anionic polyelectrolyte for forming a coacervate with a polyvalent cation has an average molecular weight (weight average Mw) of from 3 kDa to 1500 kDa.
6. The kit according to any one of claims 1 to 5, wherein the polyvalent cation is selected from the group consisting of mineral-forming cations.
7. 7. The kit according to claim 1, wherein the cationic polyelectrolyte for forming a coacervate with a polyvalent anion is selected from the group consisting of organic polyelectrolytes.
8. 8. The kit according to claim 1, wherein the cationic polyelectrolyte for forming a coacervate with a polyvalent anion has an average molecular weight (weight average Mw) of from 3 kDa to 1500 kDa.
9. 9. The kit according to claim 1, wherein the polyvalent anion is selected from the group consisting of mineral-forming anions, and partially organically modified silicates, sulfates, tungstates, vanadates, molybdates, and carbonates.
10. The kit according to any one of claims 1 to 9, wherein the proportion of the coacervate component is 1% by weight or more.
11. The kit according to any one of claims 1 to 10, which is a solid.
12. The kit according to any one of claims 1 to 10, which is a liquid and / or an emulsion and / or a suspension.
13. The kit according to any one of claims 1 to 10, which is a gel.
14. The kit according to any one of claims 1 to 10, which is a paste.
15. The kit according to any one of claims 1 to 14, comprising 1 to 100 wt % of partner ions and coacervates.
16. The kit according to any one of claims 1 to 15, further comprising water.
17. The kit according to any one of claims 1 to 16, wherein the coacervate has a water content of 0.1 to 90 wt %.
18. The kit according to any one of claims 1 to 17, wherein the concentration of the polyelectrolyte and its counterion that form the coacervate in the coacervate is 10 to 100 wt %.
19. The kit according to any one of claims 1 to 18, comprising a fluoride ion as a partner ion.
20. A kit according to any one of claims 1 to 19, wherein the partner ions are present in the dental material in a substantially soluble form.
21. The kit according to any one of claims 1 to 20, which is self-curing.
22. 22. The kit according to any of the preceding claims, having a working time and / or setting time according to ISO 9917:2007 of 1 min to 5 min.
23. A kit according to any of the preceding claims, wherein the hardened dental material is self-bonding.
24. The kit according to any of the preceding claims, wherein the hardened dental material has a compressive strength of 50 or more and a flexural strength of 20 or more according to ISO 9917:2007.
25. The kit of any one of claims 1 to 24, wherein at least one of the components is a solid.
26. A kit according to any preceding claim, wherein at least one of the components is liquid.
27. A kit according to any preceding claim, wherein at least two of the components are pastes.
28. The kit of any one of claims 1 to 25, wherein at least two components are gels.
29. 29. The kit of any of claims 1 to 28, wherein at least one of the components has a pH of 7 to 10 at 23°C.
30. A kit according to any preceding claim, further comprising a further component c.
31. A kit according to any of the preceding claims, wherein components a and b are contained in a device suitable for mixing and / or in a multi-compartment cartridge as part of a cartridge system for extruding the components through a mixing needle.
32. 32. The kit of any one of claims 1 to 31, wherein one of the partner ions is multivalent and is included in the coacervate as a counterion, a second partner ion is included in the aqueous solution, and at least one of the components further comprises a second polyelectrolyte having a different charge than the polyelectrolyte of the coacervate.
33. 32. The kit according to any one of claims 1 to 31, wherein component a comprises at least one first coacervate powder comprising an alkaline earth metal ion as a counter ion and at least one second coacervate powder comprising a polyvalent anion as a partner ion.
34. For treating defects in dental hardness, Steps below: i. applying component b to the dentin and / or enamel; ii. applying component a together with component b to the dentin and / or component b to the enamel; The kit according to any one of claims 1 to 33, for use in a method comprising the steps of:
35. For treating defects in dental hardness, Steps below: i. mixing component a with component b; ii. applying the mixture to dentin and / or enamel; The kit according to any one of claims 1 to 33, for use in a method comprising the steps of:
36. A kit according to any one of claims 1 to 35 for use as a sealant, coating, reline and / or filler.
Citation Information
Patent Citations
Method for promoting recalcification of tooth
JP2007099632A
Fluoride compositions and methods for tooth mineralization
JP2009525988A
Adhesive composite coacervates and methods for their preparation and use.
JP2011510152A
Adhesive composite coacervates and methods for preparing and using them
JP2013500072A
Simple adhesive coacervate, as well as its manufacturing method and use.
JP2014502296A